Fatores de ambiência numa escola pública municipal no interior da Bahia - MACHADO , Juliana Fernandes (2017)
In Brazil public buildings consume 8% of all the energy produced, since in the same are used outdated equipment, with great energy consumption and also does not take advantage of ventilation and natural lighting. The country's public schools are usually designed and constructed, disregarding the use of natural resources such as the sunshine course and direction of the winds, indispensable aspects for the users in the performance of activities, due to the thermal discomfort as well as the restriction of natural luminosity. The lighting, among the parameters of environmental comfort, stands out for affecting the individual physically and psychologically. The planning and achievement of the use of natural light brings benefits in student productivity and economics. In this work the environmental comfort and the perception of the users in a municipal public school in the interior of Bahia were qualified. Measurements of temperature and relative humidity, brightness and noise were carried out in two classrooms at three different times. The questionnaire elaborated was applied to 115 students, seeking their perception of environmental comfort. It was observed in the experimental conditions in situ, that the evaluated rooms presented deficient conditions both in the measurements and in the perception of environmental quality. The demand for architectural projects, execution or constructive renovation is considered, considering geographic orientation and design, taking advantage of natural lighting and ventilation, increasing environmental health, school performance and energy efficiency